Advancing citizenship through language arts education: conceptions of rhetoric in Scandinavian national curricula. Issue 4 (4th July 2022) - Hogarth, Claire; Matthiesen, Christina; Bakken, Jonas
ABSTRACT: Scandinavian countries have a long tradition of widespread public schooling linked to civic education. In the most recent curriculum reforms, concepts from rhetoric appear in various forms in language arts subject curricula from primary to upper-secondary school. In this article, we examine how current Scandinavian curricula reflect rhetoric and rhetorical education through content analysis based on David Fleming's update of the classical triad in rhetorical education. We examine explicit and implicit references to rhetorical art, practice, and inquiry to gain insight into how rhetoric is reflected and conceptualized in national curricula, thereby providing a nuanced outlook for future research on the rhetorical turn of education. The analysis shows that the curricula for language arts subjects in all Scandinavian countries include several key components of contemporary rhetorical education, and in Swedish and Norwegian curricula, rhetoric is also explicitly linked to the development of democratic citizenship. However, references to rhetoric in curricula documents are sometimes implicit, and the explicit references that are present might give the impression that rhetoric should be taught only as a technical skill devoid of context or as critical text analysis.